Tithonian ammonoids (Cephalopoda, Ammonoidea) from the Vaca Muerta Formation, Neuquén Basin, West-Central Argentina - Vennari, Verónica Vanesa (2016)
Ammonoids are the most abundant and diverse group of marine invertebrates present in the Vaca Muerta Formation (early Tithonian - early Valanginian) of the Neuquén Basin (west-central Argentina). A modern systematic review of the late early Tithonian - early middle Tithonian ammonoids of the Vaca Muerta Formation was conducted, focusing on perisphinctids (Superfamily Perisphinctoidea) the main components of the ammonoid assemblages. This revision was based on new fields collections and the assessing of reference type material. As a result, nine species included in four genera are identified, described and grouped into one family (Ataxioceratidae) and two subfamilies (Lithacoceratinae and Virgatosphinctinae). Subfamily Lithacoceratinae is represented by the monospecific genus Indansites (gen. nov.) and the species I. malarguensis Spath, 1925. Subfamily Virgatosphinctinae includes the genus Virgatosphinctes Uhlig, 1910b with V. andesensis (Douvillé, 1910a) and V. (?) densistriatus (Steuer, 1897); the genus Pseudinvoluticeras Spath, 1925 with P. douvillei Spath, 1925 and Pseudinvoluticeras primordialis n. sp.; and the genus Choicensisphinctes Leanza, H. 1980 with Ch. choicensis (Burckhardt, 1903), Ch. erinoides (Burckhardt, 1903), Ch. n. sp. aff. Ch. erinoides and Ch. aconcaguensis n. sp. The new name Virgatosphinctes andesensis Assemblage Zone is here proposed to replace the former Virgatosphinctes mendozanus Assemblage Zone of the Andean Tithonian. Also, a tentative biostratigraphic subdivision of this biozone into two consecutive Interval Subzones, Pseudinvoluticeras primordialis to the base and Indansites malarguensis to the top, is proposed. Both Interval Subzones can be partially correlated with Darwini and Semiforme Zones of the European standard, indicating a late early Tithonian - early middle Tithonian age for the V. andesensis Assemblage Zone. In addition, synchronicity of the Tithonian transgression in the Neuquén Basin is sustained through the existence of a taxonomically homogeneous ammonoid assemblage in the lower portion of all the Vaca Muerta Formation sections studied.